Neurological tests improve after Olympic-style boxing bouts: a pretournament and post-tournament study in the 2016 Women`s World Boxing Championships - Howell, D. R.; Meehan, W. P.; Loosemore, M. P.; Cummiskey, J.; Grabner von Rosenberg, J. P.; McDonagh, D. (British Journal of Sports Medicine, 2017)
Aim: To prospectively examine the neurocognitive, postural, dual-task and visual abilities of female Olympic-style boxers before and after participation in a tournament.